2017
DOI: 10.1007/s12272-017-0991-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of acacetin on sepsis-induced acute lung injury via its anti-inflammatory and antioxidative activity

Abstract: Sepsis is a clinical syndrome with no effective protective or therapeutic treatments. Acacetin, a natural flavonoid compound, has anti-oxidative and anti-inflammatory effects which can potentially work to reduce sepsis. We investigated the potential protective effect of acacetin on sepsis-induced acute lung injury (ALI) ALI and dissect out the underlying mechanisms. Mice were divided into five groups: a sham group, a sepsis-induced ALI group, and three sepsis groups pre-treated with 20, 40, and 80 mg/kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 64 publications
1
35
0
Order By: Relevance
“…Other reports showed that acacetin has anti-inflammation, anti-tumour and antioxidative properties. 24,25 Our recent studies reported that acacetin and its water-soluble prodrug confer cardioprotection against hypoxia/reoxygenation insult in cardiomyocytes 14 and ischaemia/reperfusion injury in in vivo and ex vivo hearts. 13 Acacetin prodrug significantly improves myocardial function and inhibits ventricular arrhythmia induced by ischaemia/ reperfusion injury in rats; acacetin prevents ischaemia/reperfusion by increasing myocardial antioxidation and inhibiting inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other reports showed that acacetin has anti-inflammation, anti-tumour and antioxidative properties. 24,25 Our recent studies reported that acacetin and its water-soluble prodrug confer cardioprotection against hypoxia/reoxygenation insult in cardiomyocytes 14 and ischaemia/reperfusion injury in in vivo and ex vivo hearts. 13 Acacetin prodrug significantly improves myocardial function and inhibits ventricular arrhythmia induced by ischaemia/ reperfusion injury in rats; acacetin prevents ischaemia/reperfusion by increasing myocardial antioxidation and inhibiting inflammation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Caused by trauma, shock, and infection, sepsis is one of the life-threatening situations leading to multiple organ dysfunctions and failure. ALI is one of the typical organ injuries caused by sepsis, which is characterized by lung edema and intractable hypoxemia [ 17 ]. The molecular mechanisms of ALI are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that oxidative stress plays important role in endothelial dysfunction, lung disease, gastrointestinal dysfunction, and atherosclerosis, and inflammatory symptoms are involved in all these disorders [ 112 , 113 ]. Excessive pro-inflammatory cytokines and mitochondrial dysfunction induce oxidative stress, characterized by an imbalance between the effectiveness of antioxidant defense and the speed of ROS generation, causing a net overload of oxidants [ 114 , 115 , 116 ].…”
Section: Anti-inflammatory Molecules Of Medicinal Plants and Mechamentioning
confidence: 99%